Analisis Efektifitas Dan Efisiensi Penggunaan Anggaran Belanja Barang / Operasional Pada Kantor Unit Penyelenggara Pelabuhan Serui - Abdilla, Abdilla; Adriansyah, Adriansyah (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2024)
The Serui Port Organizing Unit Office, as part of the Ministry of Transportation, Directorate General of Sea Transportation, is a government entity that is obliged to carry out its duties with transparency, effectiv, efficiency and professionalism. This research aims to investigate the efectiveness and efficiency of budget use at the Serui Port Organizing Unit Office (UPP Serui), the factors that influence it, as well as the impact of the use of information technology and government budget policies. The research method used is quantitative by analyzing data from UPP Serui's financial reports in a certain period. Descriptive analysis is used to evaluate budget allocations and expenditure realization, while regression analysis is used to identify factors that influence efficiency. The research results show that economic growth, political stability, and economic size have a significant influence on the effectiveness and efficiency of budget use, while inflation is not significant. Apart from that, government budget policy also plays an important role in determining the efficiency of budget use at the UPP Serui Office.